PENENTUAN SIFAT MEKANIS SERAT SABUT KELAPA - Bakri, Bakri (Jurnal MEKANIKAL, 2010)
Coir fibres are obtained from coconut husk. In application of composite materials, coir fibres are influenced by mechanial properties. This study aims to characterize the mechanical properties of coir fibres. To characterize mechanial properties of coir fibres, variation of gauge length of fibres was conducted. The result showed that variability of cross setional areas influenced mechanical properies and that the Young’s modulus, breaking stress and breaking strain can be determined.